Cardioprotective Effect of Cilostazol on Ischemia-Reperfusion Injury Model - Sahin,Mazlum (2022)
Abstract Introduction: To clarify the potential protective role of cilostazol on rat myocardial cells with ischemia-reperfusion injury (IRI) models. Methods: The study was conducted with three groups of 10 Wistar rats (control group, rats without any coronary ischemia; sham group, rats with coronary ischemia but without cilostazol administration; and cilostazol group, rats with coronary ischemia and cilostazol administration). The level of myocardial injuries was measured by analyzing cardiac troponin T and creatine kinase MB levels in blood samples. In tissue samples, adenosine triphosphate (ATP), nitric oxide, superoxide dismutase (SOD), and malondialdehyde were used to determine the amount of tissue damage. Tissues were stained with hematoxylin-eosin method, and samples were examined under light microscope. Results: The mean level of ATP was 104.4 in the cilostazol group and 149.1 in the sham group (P=0.044). SOD level was significantly higher in the cilostazol group than in the sham group (2075.3 vs. 1783.7, P=0.043). According to histopathological examination, all samples were classified as G0 in the control group. In the sham group, one sample was categorized as G1, six samples as G2, and three samples as G3. In the cilostazol group, nine samples and one sample were categorized as G1 and G2, respectively (P=0.011). Conclusion: Cilostazol has beneficial effects on Wistar rats’ myocardial cells in regard to decreasing inflammatory process, necrosis, and fibrosis. Our findings revealed that the use of cilostazol significantly decreased ATP and increased SOD levels in Wistar rats’ myocardial cells after IRI.